Photography, Media Ecology and the Method of Paulo Freire: The Contemporary View - Reno, Denis [UNESP]; Guimaraes-Guedes, Denise [UNESP] (Univ Nacional Colombia, Fac Ciencias Humanas, 2021)
Considering the new multi-platform forms of communication and concepts about media ecology, this article proposes the adoption of photography as a pedagogical instrument in the construction of knowledge in subjects in the humanist area, based in Paulo Freire concepts. We present the proposal for the training of a professional who is safe, sensitive, and attentive to reality in your environment, with a critical gaze and aware of his role in the construction of citizenship, highlighting the importance of the image and the use of the New New Media (Levinson, 2012).
Keywords: communication; education; media ecology; Paulo Freire; photography; work